2007
DOI: 10.1291/hypres.30.1219
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blocker Reduces Oxidative Stress and Attenuates Hypoxia-Induced Left Ventricular Remodeling in Apolipoprotein E-Knockout Mice

Abstract: Elevated superoxide formation in cardiac extracts of apolipoprotein E-knockout (apoE-KO) mice has beenreported. In addition, we previously reported that hypoxia increased oxidative stress in the aortas of apoE-KO mice, although we did not examine the effect of hypoxia on the heart. The aim of this study was to inves-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 47 publications
(29 reference statements)
1
52
0
1
Order By: Relevance
“…8 We speculated that the inhibitory effects of losartan on LPS-induced proinflammatory gene expression were mediated by IkK-IkB-NFkB signaling because studies showed that AT1R blockers exerted antiinflammatory effects by suppressing IkK-IkB-NFkB activation. 15,16 However, our data show that losartan has no effect on LPS-induced IkB phosphorylation, suggesting that losartan does not inhibit LPSinduced signaling through the IkK-IkB-NFkB pathway, at least at the level of NF-kB activation.…”
Section: Discussionmentioning
confidence: 56%
“…8 We speculated that the inhibitory effects of losartan on LPS-induced proinflammatory gene expression were mediated by IkK-IkB-NFkB signaling because studies showed that AT1R blockers exerted antiinflammatory effects by suppressing IkK-IkB-NFkB activation. 15,16 However, our data show that losartan has no effect on LPS-induced IkB phosphorylation, suggesting that losartan does not inhibit LPSinduced signaling through the IkK-IkB-NFkB pathway, at least at the level of NF-kB activation.…”
Section: Discussionmentioning
confidence: 56%
“…Briefly, in nucleated transverse sections stained with hematoxylin-eosin, cardiomyocytes with both a clear nucleus and intact cellular membrane were measured using NIS-Elements version 3.07 software (Nikon), and at least 30 cardiomyocytes were analyzed per heart. After staining with Sirius red, color images were randomly selected from five high-power fields (at a magnification of ϫ200), and the collagen volume ratio (%) was calculated as described elsewhere (33). The LV free wall myocardium was fixed in 4% paraformaldehyde containing 0.25% glutaraldehyde and 4.5% sucrose.…”
Section: Animalsmentioning
confidence: 99%
“…Inhibiting both angiotensin II type 1 and type 2 receptors with Sar1-Ile8-Ang II reduces collagen type I and elastin deposition but also increases vascular stiffness, fibronectin, and MMP-2 activity [115]. Olmesartan improves LV remodeling in apo E null mice by inhibiting nuclear factor -B (NF-B) and MMP-9 activities [116]. Yang and colleagues reported that valsartan decreased levels of MMP-2, -3, and -9 post-MI [117].…”
Section: Ace Inhibitors and Angiotensin II Receptor Inhibitors-angiotmentioning
confidence: 99%